Longitudinal Reproducibility of MR Perfusion Using 3D Pseudocontinuous Arterial Spin Labeling With Hadamard‐Encoded Multiple Postlabeling Delays. Issue 6 (30th November 2019) - Cohen, Alexander D.; Agarwal, Mohit; Jagra, Amritpal S.; Nencka, Andrew S.; Meier, Timothy B.; Lebel, R. Marc; McCrea, Michael A.; Wang, Yang
Abstract : Background: Arterial spin labeling (ASL) can be confounded by varying arterial transit times (ATT) across the brain and with disease. Hadamard encoding schemes can be applied to 3D pseudocontinuous ASL (pCASL) to acquire ASL data with multiple postlabeling delays (PLDs) to estimate ATT and then correct cerebral blood flow (CBF). Purpose: To assess the longitudinal reproducibility of 3D pCASL with Hadamard‐encoded multiple PLDs. Study Type: Prospective, longitudinal. Population: Fifty‐two healthy, right‐handed male subjects who underwent imaging at four timepoints over 45 days. Field Strength/Sequence: A Hadamard‐encoded 3D pCASL sequence was acquired at 3.0T with seven PLDs from 1.0–3.7 sec. Assessment: ATT and corrected CBF (cCBF) were computed. Conventional uncorrected CBF (unCBF) was also estimated. Within‐ and between‐subject coefficient of variation (wCV and bCV, respectively) and intraclass correlation coefficient (ICC) were evaluated across four time intervals: 7, 14, 30, and 45 days, in gray matter and 17 independent regions of interest (ROIs). A power analysis was also conducted. Statistical Tests: A repeated‐measures analysis of variance (ANOVA) was used to compare ATT, cCBF, and unCBF across the four scan sessions. A paired two‐sample t ‐test was used to compare cCBF and unCBF. Pearson's correlation was used to examine the relationship between the cCBF and unCBF difference and ATT. Power calculations were completed using both the cCBF and unCBF variances. Results: ATT showed the lowest wCV and bCV (3.3–4.4% and 6.0–6.3%, respectively) compared to both cCBF (10.5–11.7% and 20.6–22.2%, respectively) and unCBF (12.0–13.6% and 22.7–23.7%, respectively). wCV and bCV were lower for cCBF vs. unCBF. A significant difference between cCBF and unCBF was found in most regions ( P = 5.5 × 10 ‐5 –3.8 × 10 ‐4 in gray matter) that was highly correlated with ATT (R 2 = 0.79–0.86). A power analysis yielded acceptable power at feasible sample sizes using cCBF. Data Conclusion: ATT and ATT‐corrected CBF were longitudinally stable, indicating that ATT and CBF changes can be reliably evaluated with Hadamard‐encoded 3D pCASL with multiple PLDs. Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;51:1846–1853.